Autobiographical Genre and Autobiography as a Form of Revealing the Theme of Childhood and Adolescence - Ghazaryan, Ruzan (Bulletin of Yerevan University B: Philology, 2025)
This article explores the principle of autobiographical writing in Russian literature during the transition from Romanticism to Realism, focusing on key works by Alexander Pushkin and Mikhail Lermontov, as well as later examples from Charles Dickens, Leo Tolstoy, Mark Twain, and J.D. Salinger. It argues that the construction of autobiographical narratives not only reflects the authors' personal experiences but also serves as a lens through which broader societal attitudes—particularly regarding childhood—are examined and critiqued. The novelty of this study lies in its comparative analysis of how different literary traditions grapple with the theme of childhood as both a source of innocence and a site of conflict. By investigating the evolution of autobiographical elements, the article highlights the complexities of character construction and narrative form across cultures. Key problems addressed include the persistent societal attitudes towards children and the moral implications of these views as reflected in literature. The study aims to elucidate how the autobiographical genre serves as a vehicle for exploring identity, innocence, and the tensions between individual experience and societal norms. Ultimately, this research seeks to contribute to the understanding of the interplay between autobiographical writing and thematic development in literature, revealing how the personal is intricately linked to the collective consciousness of a given era.
Keywords: autobiographical writing; Russian literature; romanticism; realism; childhood; character construction; societal norms; identity; moral development